Non Equivalence at Scientific Terms in Mathematics Bilingual Textbook - Tarigan, Fatin Nadifa; Juliana, Juliana (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2019)
This study entails the translation of scientific terms from English into Indonesian. The objectives of this study are to investigate the problem of non-equivalence at word level found in mathematics bilingual textbook and to investigate the translation strategies used. This study was conducted by using descriptive qualitative design. The data of this study were 89 words and phrases containing scientific terms. The data were collected through documentary technique. The technique of data analysis was interactive model. The finding of this study revealed that there were five problems of non-equivalence at scientific terms found in mathematics bilingual textbook. They were the source language concept is not lexicalized in the target language, the source language word is semantically complex, the source and target language make distinction in meaning, the target language lacks hyponym,Ã‚Â  and difference in form. To solve the problems of non equivalence, it was found that four translation strategies proposed by Baker were applicable.